Countablock - Franceschelli, Christopher; Abrams, Harry N.; Peskimo (Firm) (New York : Abrams Appleseed, 2014)
Teaches the numbers from one to one hundred by showing how a certain number of objects can become something else, from one acorn growing into an oak tree to one hundred puzzle pieces becoming one large puzzle.
Title from cover.
On board pages.
Keywords: Counting -- Fiction; Toy and movable books; Board books; Counting -- Juvenile literature